2022
DOI: 10.15252/embj.2022111608
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of SARS‐CoV‐2 replication and associated inflammation by concomitant targeting of viral and host cap 2'‐O‐ribose methyltransferases

Abstract: The SARS‐CoV‐2 infection cycle is a multistage process that relies on functional interactions between the host and the pathogen. Here, we repurposed antiviral drugs against both viral and host enzymes to pharmaceutically block methylation of the viral RNA 2'‐O‐ribose cap needed for viral immune escape. We find that the host cap 2'‐O‐ribose methyltransferase MTr1 can compensate for loss of viral NSP16 methyltransferase in facilitating virus replication. Concomitant inhibition of MTr1 and NSP16 efficiently suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 135 publications
(238 reference statements)
4
23
0
Order By: Relevance
“…Since both the effects were similar in magnitude, it is tempting to speculate that the effect of type I IFN on wt virus is mediated by upregulation of additional, unknown ISGs targeting SARS–CoV‐2 replication. In addition, we found that the absence of the cellular 2′‐O‐methyltransferase MTR1 resulted in reduced replication of wt SARS–CoV‐2 and in a complete block to Nsp16mut replication (Fig 6E ; Bergant et al , 2022 ). This further underlines the importance of RNA 2′‐O‐methylation for viral replication and suggests that the cellular methyltransferase MTR1 can partly compensate for the loss of the viral enzyme in SARS–CoV‐2 Nsp16mut.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Since both the effects were similar in magnitude, it is tempting to speculate that the effect of type I IFN on wt virus is mediated by upregulation of additional, unknown ISGs targeting SARS–CoV‐2 replication. In addition, we found that the absence of the cellular 2′‐O‐methyltransferase MTR1 resulted in reduced replication of wt SARS–CoV‐2 and in a complete block to Nsp16mut replication (Fig 6E ; Bergant et al , 2022 ). This further underlines the importance of RNA 2′‐O‐methylation for viral replication and suggests that the cellular methyltransferase MTR1 can partly compensate for the loss of the viral enzyme in SARS–CoV‐2 Nsp16mut.…”
Section: Discussionmentioning
confidence: 73%
“…The KO was confirmed by immunoblot and sequence analysis. A549 MTR1 KO, IFIT1 KO, and MTR1KO/IFIT1 KO have been described previously (Bergant et al, 2022). Calu-3 and Caco-2 KO cells (RIG I KO (5 0 -CACCGCAGGATGTAGGTAGGGTCCA-3 0 ), MDA5 KO (5 0 -CACCGAACTGCCT GCATGTTCCCGG-3 0 ), IFIT1 KO (5 0 -AGGCATTTCATCGTCATCAA-3 0 ), or luciferase Ctrl KO) were generated by CRISPR-Cas9 genome editing, as described above.…”
Section: Cell Culture and Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The viral 2'-O-methyltransferase Nsp16, together with the N7 methyltransferase activity of Nsp14, catalyzes Cap-1 modification of viral RNA to mimic host mRNA, thereby escaping detection by MDA5. In accord, inhibiting viral and cellular methyltransferase activities during SARS-CoV-2 infection elevated antiviral gene expression and restricted viral replication [43] . The endoribonuclease activity of Nsp15 can cleave and limit the accumulation of polyuridine-containing negative-sense viral RNAs activating MDA5 during mouse hepatitis virus infection [44] ; whether an analogous immune escape mechanism is utilized by SARS-CoV-2 requires further exploration.…”
Section: Ifn Antagonism By Sars-cov-2 and Iavmentioning
confidence: 95%
“…Viral mRNA is synthesized by PB1 by using the cleaved host-derived nucleotides with cap as a primer ( 5 , 6 ). By contrast, non–cap-snatching viruses such as coronaviruses, poxviruses, and flaviviruses encode their own cap-binding 2′-O-MTases and mediate 2′-O-methylation of their RNA to imitate the cellular cap and evade recognition by antiviral sensors ( 7 , 8 ). Cellular MTr1 deficiency leads to the accumulation of host cap0 RNAs in the cytoplasm ( 2 ) and potentially activates RIG-I and IFIT1 ( 3 , 4 ).…”
mentioning
confidence: 99%